EFIKASI HERBISIDA PARAKUAT DIKLORIDA 276 g/l TERHADAP PENGENDALIAN GULMA PADA BUDIDAYA KAKAO BELUM MENGHASILKAN - Susanto, Herry; Aslamiah, Aslamiah; Evizal, Rusdi; Pujisiswanto, Hidayat (Universitas Lampung, 2025)
The growth of weeds in immature cocoa plants is highly susceptible to competition for water, nutrients, and light, which can disrupt the growth of cocoa plants. Efforts to manage cocoa cultivation include weed control using the chemical herbicide paraquat dichloride, a non-selective contact herbicide. This study aimed to determine the effective dosage of paraquat dichloride for controlling weeds in immature cocoa plants, changes in weed composition, and phytotoxicity on immature cocoa plants following the application of paraquat dichloride. The study was conducted in Talang Sepuh Village, Talang Padang Sub-district, Tanggamus Regency, from March–May 2024. The research employed a Randomized Complete Block Design (RCBD) with six treatments and four replications. Treatments included paraquat dichloride at doses of 414 g/ha, 552 g/ha, 690 g/ha, 828 g/ha, mechanical weeding, and a control group (no weed control). Data variance homogeneity was tested using Bartlett's test, and data additivity was evaluated with Tukey's test. If the assumptions were met, the mean difference was analyzed using the Least Significant Difference (LSD) test at a 5% significance level. The results indicated that paraquat dichloride at doses of 414–828 g/ha effectively controlled total weeds, broadleaf weeds, and dominant weeds (Eleusine indica, Praxelis clematidea, and Synedrella nodiflora). Meanwhile, doses of 552–828 g/ha were effective in controlling grass weeds and dominant weeds (Ottochloa nodosa and Asystasia gangetica). The application of paraquat dichloride did not alter weed composition and did not cause phytotoxic effects on immature cocoa plants..Keywords : Herbicide, Paraquat dichloride, Weed, Immature cocoa.